Systematic study of effect of cross-drafts and nozzle diameter on shield gas coverage in MIG welding. (1st November 2013) - Beyer, V; Campbell, S W; Ramsey, G M; Galloway, A M; Moore, A J; McPherson, N A
<x xml:space="preserve">Abstract</x> A shield gas flowrate of 15-20 L min−1 is typically specified in metal inert gas welding, but is often adjusted to as high as 36 L min−1 by welders in practice. Not only is this overuse of shield gas wasteful, but uncontrolled high gas flows can lead to significant turbulence induced porosity in the final weld. There is therefore a need to understand and control the minimum shield gas flowrate used in practical welding where cross-drafts may affect the coverage. Very low gas coverage or no shielding leads to porosity and spatter development in the weld region. A systematic study is reported of the weld quality achieved for a range of shield gas flowrates, cross-draft speeds and nozzle diameters using optical visualisation and numerical modelling to determine the shield gas coverage. As a consequence of the study, the shield gas flow has been reduced to 12 L min−1 in production welding, representing a significant process cost saving and reduced environmental impact with no compromise to the final weld quality.